Hubungan Pengetahuan dan Sikap K3 terhadap Perilaku K3 di Bengkel Pemesinan SMK Negeri 5 Padang (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to (1) the relationship between K3 knowledge and K3 behavior; (2) the relationship between K3 attitudes and K3 behavior; (3) the relationship between K3 knowledge and K3 attitudes and K3 behavior in the workshop of SMK Negeri 5 Padang. This study uses the expost facto method, the data obtained are interval and nominal data. This study uses three types of variables, 1) K3 knowledge variable (X1), 2) K3 attitude variable (X2) and 3) K3 behavior variable (Y). Data collection techniques use questionnaires, observations. The population and sample in this study were students of the Mechanical Engineering Department, Class XI, SMK Negeri 5 Padang, totaling 89 students, the sample was taken using the total sampling technique. The data analysis techniques used are descriptive and multiple regression. Hypothesis testing based on the results of the regression test that has been carried out, the results show that: (1) there is a positive relationship between knowledge and K3 behavior of 35.5% of class XI TPM students of SMK Negeri 5 Padang (2) there is a positive relationship between K3 attitudes and K3 behavior of 37.5% of class XI XI TPM students of SMK Negeri 5 Padang (3) there is a positive relationship between knowledge and K3 attitudes together towards K3 behavior of 40.8% of class XI TPM students of SMK Negeri 5 Padang, from the data there is a relationship between K3 Knowledge and attitudes towards K3 Behavior.